IMPLEMENTASI PENDIDIKAN KARAKTER RELIGIUS TERHADAP ANAK USIA DINI - Murniyati, Murniyati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
This study aimed at describing the Implementation of Religious Character Education on Early Childhood Education in PAUD Nusantara Kec. Sako Baru Palembang. This research was a qualitative descriptive study. Data were collected through observation, interview and documentation. The results of this study showed that religious character education can change attitudes and behavior of students towards the better. Character education is a system of cultivating character values that include components of knowledge, awareness and actions to implement those values. The development and implementation of religious character education should be carried out according to the implementation of religious character education from an early age so that students are expected to master themselves in accordance with the norms of religion.